Isolated bilateral pleural effusion as the sole manifestation of late onset ovarian hyperstimulation syndrome - Shalu Gupta; Balasubramaniam Sathya; Nabaneeta Padhy; Shankar Kundavi; Betty E Thomas; Thangam R Varma (Wolters Kluwer Medknow Publications, 2009)
To report a case of late onset ovarian hyperstimulation with bilateral pleural effusion and respiratory distress as the sole manifestation after embryo transfer.